Lessons learned about prevalence and growth rates of abdominal aortic aneurysms from a 25-year ultrasound population screening programme. Issue 1 (19th December 2017) - Oliver-Williams, C; Sweeting, M J; Turton, G; Parkin, D; Cooper, D; Rodd, C; Thompson, S G; Earnshaw, J J
Abstract: Background: This study aimed to assess how the prevalence and growth rates of small and medium abdominal aortic aneurysms (AAAs) (3·0–5·4 cm) have changed over time in men aged 65 years, and to evaluate long-term outcomes in men whose aortic diameter is 2·6–2·9 cm (subaneurysmal), and below the standard threshold for most surveillance programmes. Methods: The Gloucestershire Aneurysm Screening Programme (GASP) started in 1990. Men aged 65 years with an aortic diameter of 2·6–5·4 cm, measured by ultrasonography using the inner to inner wall method, were included in surveillance. Aortic diameter growth rates were estimated separately for men who initially had a subaneurysmal aorta, and those who had a small or medium AAA, using mixed-effects models. Results: Since 1990, 81 150 men had ultrasound screening for AAA (uptake 80·7 per cent), of whom 2795 had an aortic diameter of 2·6–5·4 cm. The prevalence of screen-detected AAA of 3·0 cm or larger decreased from 5·0 per cent in 1991 to 1·3 per cent in 2015. There was no evidence of a change in AAA growth rates during this time. Of men who initially had a subaneurysmal aorta, 57·6 (95 per cent c.i. 54·4 to 60·7) per cent were estimated to develop an AAA of 3·0 cm or larger within 5 years of the initial scan, and 28·0 (24·2 to 31·8) per cent to develop a large AAA (at least 5·5 cm) within 15 years. Conclusion: The prevalence of screen-detected small and medium AAAs has decreased over the past 25 years, but growth rates have remained similar. Men with a subaneurysmal aorta at age 65 years have a substantial risk of developing a large AAA by the age of 80 years. Abstract : Growth rates unchanged but prevalence decreasing